Evaluation of dentists’ awareness, knowledge, and clinical practices regarding early-stage oral cancer lesions in Türkiye: A cross-sectional study - Sayna Behkar; Paniz Golchini; Ömer Faruk Kocamaz; Serpil Altundoğan (PLoS ONE, 2026)
This cross-sectional study aimed to evaluate dentists’ awareness, knowledge, and clinical practices regarding early-stage oral cancer lesions, with an emphasis on diagnostic behavior, patient education, and referral approaches. A total of 263 dentists from public and private institutions in Ankara, Türkiye, participated in the survey, which included a content-validated 36-item questionnaire covering demographic data, examination habits, knowledge of lesion features, biopsy practices, and educational experience. The data were analyzed via descriptive statistics, chi-square tests, and Monte Carlo simulations to explore associations between professional characteristics and clinical behaviors. While 78% of the participants acknowledged the dentist’s role in reducing oral cancer mortality, only 17.5% reported performing routine oral cancer screenings. Biopsy practice was limited, with only 11% indicating that they had ever performed a biopsy, and 36.9% preferred to monitor lesions instead of referring them immediately. Experienced dentists were significantly more likely to examine their lymph nodes (p = 0.006) and conduct routine screenings (p < 0.001). Although tobacco and alcohol use are widely recognized as risk factors, only 27.7% of the participants routinely examined high-risk anatomical areas. Patient education was reported by 92.4% of the participants, but brochures and visual aids were rarely used. Fewer than one-third of the participants rated their undergraduate training on oral cancer as sufficient, and most supported mandatory continuing education. The findings reveal considerable gaps in dentists’ preparedness and implementation of early detection strategies despite high awareness levels. Strengthening diagnostic education in undergraduate programs and promoting structured continuing education may improve early detection efforts and reduce oral cancer-related morbidity and mortality.